A study on the use of clincal practice guidlines (CPG) on management of type 2 diabetes mellitus in Kelantan - A.Rahman, Nor Azlina (2007)
INTRODUCTION The prevalence of diabetes is increasing in Malaysia. Majority of the patients were reported to have poor glycaemic control. CPG were developed to improve the practice of health care providers for better health outcomes in patients. OBJECTIVE The objective of this study was to determine the use of diabetic CPG among diabetes care team (DCT), to evaluate the effectiveness of intensive training on the CPG given to DCT in Kelantan on their knowledge, attitude and practice (KAP) and patients' KAP and diabetic control, and to determine the factors associated with HbAtc levels in type 2 diabetic patients with poor control in Kelantan. METHODS This study was conducted in all health centres (HC) in Kelantan from August 2005 till March 2006. Cross-sectional study design was used to determine the characteristics of DCT and their use of diabetic CPG, and the characteristics of type 2 diabetic patients with poor control and the factors associated with their HbAtc levels. To determine the effect of intensive course on diabetic CPG given to DCT on their KAP and their patients' KAP and diabetic control, randomised controlled trial was used where the participants were randomized into intervention and control group by cluster according to the districts in Kelantan. The participants were all DCT members and diabetic patients with poor control. Post-intervention data were collected four months after the intervention was completed. RESULTS A total of 176 DCT members participated in this study. Most of the participants knew about the existence of diabetic CPG (79. 5%) or have ever read it (71. 6% ). In term of the use of CPG, only 40.4% to 83.1% of them claimed always practice according to the diabetes care measured. The mean total knowledge scores were 23.6 marks (SD = 3.41) from the total score of 30 or 78. 7%, and the median total attitude and practice scores were 29 (IQR = 8) from the total score of 35 and 27 marks (IQR = 4) from the total score of30 or 82.9% and 90%, respectively. A total of 208 diabetic patients with poor control participated in this study. Their mean total practice scores were 21.9 (SD = 2.49) from the total score of 32 or 68.4%, and the median of total knowledge and attitude scores were 42 (IQR = 8) from the total score of 48 and 14 (IQR = 2) from the total score of IS or 87.5% and 93.3%, respectively. Patients who were married, had no formal education and receiving their diabetic care in HC without Family Medicine Specialist (FMS) were significantly associated with poorer HbAtc levels. Fasting blood glucose (FBG) levels were significantly increased with increasing levels ofHbAtc· A total of 88 DCT participants in intervention and 55 in control group completed this study. In the intervention group, significant improvement was observed in knowledge scores as compared to control group. A total of 86 patient participants in each group completed this study. Their practice scores were significantly reduced more in intervention compared to control group. However the changes observed here were minimal. No significant changes were observed in all the other outcome variables measured in DCT or patient participants. CONCLUSION Majority of the DCT members in Kelantan knew about the existence of diabetic CPG. However, their use of the CPG was not very satisfactory. The KAP ofDCT and patients were quite good but that did not translate into good diabetic control of the patients. Factors associated with HbAtc levels in the diabetic patients with poor control FBG, educational level, marital status and receiving care in HC with FMS. After intervention, significant improvement was only seen in the knowledge score ofDCT, albeit minimal. One day intensive course may not be enough to change DCT' s KAP and regularly structured continuing medical education (CME) might be needed to reinforce their KAP. Four months duration may not be enough for the DCT to properly manage their diabetic patients for observable changes in the patients' KAP and diabetic control measures.